Analisis Tren Lifestyle “Skena” Dalam Kerangka Sosial Budaya Pada Era Modern - Halimah Nur Churil Aini; Meydina Tri Luvianasari; Maris Jennet Landicho; Selvia Deva Saputri (Lembaga Pengembangan Kinerja Dosen, 2024)
Life in the modern era is characterized by rapid lifestyle changes, including the 'skena' trend that becomes an integral part of student culture at the University of Jember. This research aims to analyze the lifestyle trend